Sales Taxation, Spatial Agglomeration, and the Internet - David R. Agrawal; David E. Wildasin (Center for Economic Studies and ifo Institute (CESifo), 2019)
Technological innovations facilitating e-commerce have well-documented effects on consumer behavior and firm organization in the retail sector, but the effects of these new transaction technologies on fiscal systems remain unknown. By extending models of commodity tax competition to include urban spatial structure (agglomeration) and online commerce, one can analyze strategic tax-policy interactions among neighboring localities. Consumers buy different types of commodities, sold either by traditional or by online vendors. When the cost of online shopping falls, we show that equilibrium tax rates and revenues increase in small jurisdictions and decrease in large jurisdictions with retail shopping centers. Policy commentators warn that e-commerce erodes tax revenue - true enough for some localities - but, more accurately, changing transaction costs can generate entirely new commercial and fiscal equilibria that ultimately “redistribute” tax revenues from localities with concentrations of traditional vendors toward other, typically smaller, localities.
Keywords: H25; H71; H73; L81; R50; 330; sales tax; retail shopping; agglomeration; e-commerce; fiscal competition